3D FEM model to simulate Brownian motion inside trabecular tissue from human femoral head. Issue 5 (3rd September 2022) - Bini, Fabiano; Pica, Andrada; Novelli, Simone; Pecci, Raffaella; Bedini, Rossella; Marinozzi, Andrea; Marinozzi, Franco
ABSTRACT: The assessment of spatio-temporal distribution of water within the cancellous bone structure remains a challenging issue. In the present study, a 3D finite element model of a trabecular region with pore morphology reconstructed from micro-CT scans is developed with the aim of evaluating the dynamics of water diffusion through bone tissue. The proposed model formulates diffusion from the perspective of water particles motion. Newton's second law adapted to consider Brownian motion is used to describe particle dynamics in Lagrangian framework. The outcomes allow to investigate the temporal evolution of the water particle positions within the trabecular network. Knowledge concerning the water dynamics within the reconstructed morphology contributes to optimise the experimental setup of water uptake investigations on specific trabecular bone samples. The model could provide valuable information for the design of mimetic bone scaffolds with optimised fluid management properties.